1996
DOI: 10.1038/384276a0
|View full text |Cite
|
Sign up to set email alerts
|

20S cyclosome complex formation and proteolytic activity inhibited by the cAMP/PKA pathway

Abstract: The 20S cyclosome complex (also known as the anaphase-promoting complex) has ubiquitin ligase activity and is required for mitotic cyclin destruction and sister chromatid separation. The formation and activation of the 20S cyclosome complex is regulated by an unknown mechanism. Here we show that Cut4 (ref. 6) is an essential component of the cyclosome in fission yeast. Cut4 shares sequence similarity with BimE, a protein that regulates mitosis in Aspergillus nidulans. Mutations in cut4 result in hypersensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 23 publications
11
150
1
Order By: Relevance
“…In vitro phosphorylation of APC by PKA inhibits ubiquitination of cyclin B even in the presence of the regulatory factors Cdc20 and Cdh1/Hct1 (Kotani et al, 1998). In addition, yeast APC mutants are suppressed by mutations in the PKA pathway that lower its kinase activity (Yamashita et al, 1996). Taken together, these evidence suggests that cyclin B/cdk1-and Plk1-mediated phosphorylations induce APC activation, whereas PKA phosphorylation inhibits its activity.…”
Section: Apc Regulationsupporting
confidence: 51%
See 1 more Smart Citation
“…In vitro phosphorylation of APC by PKA inhibits ubiquitination of cyclin B even in the presence of the regulatory factors Cdc20 and Cdh1/Hct1 (Kotani et al, 1998). In addition, yeast APC mutants are suppressed by mutations in the PKA pathway that lower its kinase activity (Yamashita et al, 1996). Taken together, these evidence suggests that cyclin B/cdk1-and Plk1-mediated phosphorylations induce APC activation, whereas PKA phosphorylation inhibits its activity.…”
Section: Apc Regulationsupporting
confidence: 51%
“…Sequence analysis revealed sequence homology with the BimE (Engle et al, 1990) protein from Aspergillus nidulans and the Tgs24 murine protein (Starborg et al, 1994). Moreover, a homolog of Apc1 in fission yeast, named Cut4, has also been described as a constituent of the 20S cyclosome (Yamashita et al, 1996). The levels of Apc1 are constant throughout the cell cycle; however, regulation of this protein during mitosis seems to be exerted by phosphorylation (Peters et al, 1996;Jorgensen et al, 2001).…”
Section: Apc1mentioning
confidence: 99%
“…Although previous studies showed that Cdc13 and Cut2 could be ubiquitinated dependently on APC/C, [45][46][47] no evidence was presented for ubiquitination of Slp1 in fission yeast. We therefore attempted to test if Slp1 was ubiquitinated by following an assay previously reported.…”
Section: Resultsmentioning
confidence: 88%
“…Several regulators of the APC/cyclosome have been identi®ed. They include protein kinase A (Yamashita et al 1996 and spindle checkpoint-related Slp1 (Kim et al 1998).…”
Section: Fission Yeast Cut2/securin Degrades In Anaphasementioning
confidence: 99%